Immune snapshots along the inflammation-to-cancer road in bladder urothelium - Lu, Lingxiang; Wang, Fei; Wang, Zhenfan; Guo, Shuai; Jiang, Minjun; Ma, Zheng (Frontiers in Immunology, 2025)
The inflammatory microenvironment formed by chronic inflammation is not only a major risk factor for cancer but also a well-recognized precursor to bladder cancer. However, the immunological transitions that occur along the inflammation-to-cancer continuum remain incompletely understood. This mini-review synthesizes recent advances in understanding how the immune microenvironment evolves from an inflamed yet non-malignant urothelium to invasive carcinoma. First, we discuss how persistent stimuli—such as chronic infection or exposure to carcinogens—disrupt immune homeostasis, leading to sustained interferon signaling, cytokine secretion, and immune cell infiltration. Second, during preneoplastic and dysplastic stages, the immune landscape gradually shifts toward an environment enriched in regulatory T cells and characterized by dysfunctional cytotoxic T cells. Furthermore, in established tumors, immune evasion is primarily driven by T cell exhaustion, myeloid cell–mediated immunosuppression, and fibroblast-associated immune exclusion. Finally, advances in spatial transcriptomics, single-cell technologies, and urinary exosomal profiling have enabled precise “immune snapshots” of these transitions, providing new avenues for biomarker development and therapeutic strategy selection. Mapping these dynamic immune states holds great promise for improving risk stratification, facilitating early detection, and enabling personalized immunotherapy, ultimately translating immune snapshots into actionable strategies for bladder cancer prevention and treatment.